Art therapy in Alzheimer’s disease. An opportunity of collaboration between intersectoral public and private organizations in the co-design of health and social care services - Giusti, Martina; Persiani, Niccolò (Frontiers in Psychiatry, 2023)
Introduction The World Health Organization (WHO) has recognized art therapy as an effective supportive mechanism for the maintenance and restoration of mental health. In recent years, art therapy has been integrated in the assistance pathways of older people affected by neurocognitive disorders according to the demonstrated benefits, as no conflicts with pharmacologic treatments and the reduction of anxiety and stress. The shortage of organizational, economic, and professional resources in social-health public organizations does not allow for guaranteeing the provision of these services without the help of the private ones, not exclusively belonging to social-health sector. This research aims to investigate how the collaboration between public and private organizations of different sectors in the co-provision of non-pharmacological approaches guarantees the economic sustainability and the quality improvement of the provided services. Methods The Alzheimer Café of Prato was selected as a significant case study. Results and Discussion Art therapy programs intended for taking care of older people in the first stages of the Alzheimer’s disease have been developed, planned, supplied, and managed over the years as a result of the integration of resources, ideas, and professionals provided both by public and private sectors, the social-health sector, and cultural organizations. Conclusions The peer-to-peer co-responsibility of all organizations (public and private, from the cultural sector as well as the social and health sector) involved in the co-design of art therapy programs, not limiting their actions to only co-financing and/or co-delivery of the service, enabled the achievement of the economic sustainability of the services and the improvement of their quality.